Mary Wollstonecraft polemic with the views of Jean J. Rousseau on the upbringing and education of women - Szczap, Agnieszka (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
This article presents the views of Mary Wollstonecraft on the education of women. Her views are the essence of Enlightenment thought. She believedin the power of humanreason and the legitimacy of the slogan of the French Revolution. Proposed social reforms based on the ideas of freedom and equality, demanded the granting to womentheir civil and political rights. Sources of the programme are the theoretical assumptionsand personal experiences of the author. The philosophical foundations of liberalismwere inspired by John Locke and the polemic of views on education advocated by Jean J. Rousseau. Rousseau believed that the main task of women is pleasing men,therefore, what should be developed in them are the qualities and habits that are used to achieve this. This postulates that girls and boys were educated in a different way. Wollstonecraft referring to the universality of reason insisted on an egalitarian model of education.
Keywords: upbringing; woman; man; education; equality; reason; Enlightenment; civil rights